Alternatives to Immigration Detentions With Particular Focus on Children - Jakuleviciene, Lyra (Indonesian Journal of International Law, 2018)
Immigration detention is costly, ineffective and raises a number of human rights concerns. Numerous studies have demonstrated the detrimental effect of such detention on states and individuals. This prompted the States to search for alternative solutions that would, on the one hand – assist in reaching the objectives of migration control of foreigners on their territories, on the other – ensure that human rights of migrants and refugees are not undermined. Although various legal models of alternatives to detention (ATDs) already exist, the alternatives are still finding obstacles on their way to legislation and practice of various States. The research paper dwells into the newest developments in international law and State practice with regard to regulation, application and challenges of ATDs taking into consideration the particular situation of unaccompanied minors. It focuses on the analysis of the benefits and setbacks of ATDs available throughout different regions of the world and examines the relevance of ATD models for transit and destination countries,